2014
DOI: 10.1158/0008-5472.can-14-1106
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cancer Stem–like Cells as an Approach to Defeating Cellular Heterogeneity in Ewing Sarcoma

Abstract: Plasticity in cancer stem-like cells (CSC) may provide a key basis for cancer heterogeneity and therapeutic response. In this study, we assessed the effect of combining a drug that abrogates CSC properties with standardof-care therapy in a Ewing sarcoma family tumor (ESFT). Emergence of CSC in this setting has been shown to arise from a defect in TARBP2-dependent microRNA maturation, which can be corrected by exposure to the fluoroquinolone enoxacin. In the present work, primary ESFT from four patients contain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 29 publications
5
37
0
Order By: Relevance
“…Suspecting that enoxacin and bis-enoxacin may have undetected effects on cancer cells at lower concentrations, we first examined concentration dependence. Consistent with reports on enoxacin’s effects on other types of cancer cells 6 8 , no changes in growth parameters were detected in the presence of 50 µM of either enoxacin or bis-enoxacin. At a concentration of 100 µM, 4T1 growth was inhibited by about 40% after 4 days (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Suspecting that enoxacin and bis-enoxacin may have undetected effects on cancer cells at lower concentrations, we first examined concentration dependence. Consistent with reports on enoxacin’s effects on other types of cancer cells 6 8 , no changes in growth parameters were detected in the presence of 50 µM of either enoxacin or bis-enoxacin. At a concentration of 100 µM, 4T1 growth was inhibited by about 40% after 4 days (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Enoxacin inhibited cancer cell growth in vitro 6 , 7 , and in vivo 6 . A more recent study expanded on these results, demonstrating that enoxacin inhibited both proliferating cancer cells and cancer stem cells in Ewing’s Sarcoma, and that enoxacin acted synergistically with doxorubicin, a traditional anti-cancer agent, in the treatment of Ewing’s sarcoma in an animal model 8 . Tests of enoxacin, which crosses the blood-brain barrier, for the treatment for amyotrophic lateral sclerosis (ALS) have also provided promising results 9 .…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore EWSR1-FLI1 expression in mesenchymal cells resulted in development of ES tumors [65, 66] and EWSR1-FLI1 introduction into a population of cells enriched for osteochondrogenic progenitors derived from the embryonic superficial zone of murine long bones revealed a subpopulation of precursor cells that further enhanced EWSR1-ETS–dependent tumor induction [67]. It is yet unclear whether there is a special subfraction of precursor cells that includes the cell of origin of ES, although Stamenkovic and colleagues have reported that primary ES tumors harbor a subpopulation of cells that express CD133 constituting 3-15% of tumor cells that display the plasticity, clonogenicity and tumor-initiating capacity of tumor stem cells [68]. …”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] Logically, combination therapeutic regimens targeting both the bulk of tumor cells as well as CSCs could be an effective approach to improve long-term treatment outcomes. [ 19 ]…”
Section: Tumor Heterogeneity Overviewmentioning
confidence: 99%